Conflict of interest and funding in health communication on social media: a systematic review - Dana Al Oweini; Elie A Akl; Joanne Khabsa; Layal Hneiny; Hussein A Noureldine; Vanessa Helou; Fatima Mouzahem; Adham Makarem; Rayane El-Khoury; Razan Halak (BMJ Open)
Objectives To synthesise the available evidence on the reporting of conflicts of interest (COI) by individuals posting health messages on social media, and on the reporting of funding sources of studies cited in health messages on social media.Data sources MEDLINE (OVID) (2005–March 2022), Embase (2005–March 2022) and Google Scholar (2005–August 2022), supplemented with a review of reference lists and forward citation tracking.Design Reviewers selected eligible studies and abstracted data in duplicate and independently. We appraised the quality of the included studies using the Mixed Methods Appraisal Tool. We summarised the results in both narrative and tabular formats. We followed the PRISMA 2020 checklist for reporting our study.Results Of a total of 16 645 retrieved citations, we included 17 eligible studies. The frequency of reporting of conflicts of interest varied between 0% and 60%, but it was mostly low. In addition, a significant proportion, ranging between 15% and 80%, of healthcare professionals using social media have financial relationships with industry. However, three studies assessed the proportion of conflicts of interest of physicians identified through Open Payment Database but not reported by the authors. It was found that 98.7–100% of these relationships with industry are not reported when communicating health-related information. Also, two studies showed that there is evidence of a potential association between COI and the content of posting. No data was found on the reporting of funding sources of studies cited in health messages on social media.Conclusions While a significant proportion of healthcare professionals using social media have financial relationships with industry, lack of reporting on COI and undisclosed COI are common. We did not find studies on the reporting of funding sources of studies cited in health messages on social media.Trial registration dx.doi.org/10.17504/protocols.io.5jyl8jj4rg2w/v1.